The Influence of Financial Literacy on the Consumptive Behavior of Generation Z: A Systematic Literature Review - Rully Arestha; Camelia Camelia; Febliau Wanto; Hendy Hendy; Mutiara Mutiara (SEAN Institute, 2024)
In this article, we explore the significance of financial literacy in shaping the consumer behavior of Generation Z. Growing up in a world of technology and the internet, this generation faces unique challenges when managing their finances. Despite having access to vast information, they often struggle with impulsive and unplanned consumer behavior, leading to excessive spending. We aim to investigate the impact of financial literacy on the consumer behavior of Generation Z, with a particular focus on college students. To achieve this, we conducted a systematic literature review using secondary data from articles published on Google Scholar between 2020-2023. Our findings revealed three relevant articles that demonstrate a significant positive relationship between financial literacy and prudent consumptive behavior among Generation Z students. While lifestyle and income also play a role in financial management, financial literacy remains a critical predictor of wasteful behavior. We conclude that educational institutions and policymakers should prioritize financial literacy initiatives to equip Generation Z with the necessary skills to manage their finances effectively. Finally, our research highlights the need for comprehensive follow-up studies to compare literacy levels and consumer behavior across different tertiary institutions, providing valuable insight into developing trends and overall financial management among Generation Z.